Bilateral blood pressure differential as a clinical marker for acute aortic dissection in the emergency department. Issue 9 (18th July 2018) - Um, Sung Wook; Ohle, Robert; Perry, Jeffrey J
Abstract : Introduction: Interarm systolic BP differential is a classic sign of acute aortic dissection (AAD). All previous studies looking at the association of BP differential with AAD combine systolic BP differential >20 mm Hg with pulse deficit. Our aim was to assess the association of systolic BP differential with AAD, and its role in predicting AAD in the context of other signs and symptoms. Methods: Historical matched case–control study using patient data collected between 2002 and 2014: participants were adults >18 years old with a bilateral BP measurement presenting to two tertiary care EDs or one regional cardiac referral centre in Canada. Cases were patients with diagnosed AAD; controls were those with a triage diagnosis of truncal pain (<14 days) and an absence of a clear diagnosis on basic investigation. Cases and controls were matched in a 1:1 ratio by sex and age. Bilateral BP differential and pulse deficit were compared between groups. Results: A total of 222 patients (111 cases and 111 controls) were analysed. On univariate analysis systolic BP differential >20 mm Hg (OR 2.7, 95% CI 1.39 to 5.25) was significantly associated with AAD. Pulse deficit (diagnostic OR (DOR) 28.9) in isolation had better diagnostic accuracy than systolic BP differential >20 mm Hg in isolation (DOR 2.71) or combined with systolic BP differential >20 mm Hg (DOR 4.2). Conclusion: Bilateral systolic BP differentials >20 mm Hg are associated with non-traumatic AAD. However, the poor diagnostic accuracy and potential variability in measurement limits its clinical usefulness.